ANALISIS PENGELOLAAN DANA DESA DAN PRIORITAS PENGGUNAAN DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT DESA SINDANGKASIH DI ERA PANDEMI COVID-19 - Nisya Agniya Rahmah; Laras Pratiwi; Gista Rismayani (LP2M Universitas Perjuangan Tasikmalaya, 2021)
The priority of using village funds is the choice of activities that take precedence over other activity options to be financed with village funds. The Indonesian government allocates village funds to be managed by the village government in accordance with its authority, with the aim to improve the welfare of the community starting from the village. This research aims to find out and analyze the influence of village fund management and the priority of the use of village funds on the welfare of the people of Sindangkasih Village in the era of the Covid-19 pandemic. The research method used is a associative descriptive method with a quantitative approach. The sample in this study amounted to 100 people from Sindangkasih Village. The type of data used is primary data obtained through questionnaires. The data analysis used is multiple regression analysis. The results showed that the management of village funds and the priority of using village funds both partially and simultaneously had a significant impact on the welfare of the sindangkasih villagers in the era of the Covid-19 pandemic. This research is important because it is able to explain the factors that affect people's well-being. The novelty in this study focuses on the influence of priority use of village funds on the welfare of the community, especially the people of Sindangkasih Village.